O discurso sobre o uso do desenho de humor na educação popular (1960-1980) - Coutinho, Raissa Regina Silva (2020)
Inserted in the vast set of languages in a scenario entitled “civilization of the image”, humor design circulates through various media in our daily lives, the newspaper being one of the supports in which commonly types of drawing like the cartoon appear and make the most attractive reading. In the discursive practices of 1960-1980, the alternative press stands out for expressing humor as politicized art and in convergence with popular culture. Therefore, humor design appears as an alternative strategy for progressive forces in the face of military and conservative impositions. Unfolding as a proposal for a new language of social communication in the field of Popular Education (EP) with a liberating aspect, highlighted in documents such as ‘Vivendo e Aprendendo’ (1985), material that describes the experiences of IDAC through the works of EP during the exile of Paulo Freire, Claudius Ceccon, Rosiska and Miguel Darcy de Oliveira. A discursive network is identified in which the humor design appears as an event, whose enunciative presence is our object of research, which will be described analytically to highlight the particularities of such existence; as well as, in the need to systematize such findings to corroborate for clarification on the use of this type of visual language, according to the principles of the liberating pedagogical perspective. Thus, the objective is to analyze the discourse on the use of humor design in popular education between the 1960s and the 1980s. That said, how does the uniqueness of this discourse appear? In the midst of this study, based on the archaeological analysis of the discourse (FOUCAULT, 2012), what can be said is that there are a series of writings in this field, which appear in at least six bundles of relationships: the imagery, the humorous, the journalistic, ideopolitical, epistemological and pedagogical. The nexus with popular education, constitutes the use of humor design in its communicative function and as a representation of a typical existential situation, whose triggered domains enable guidance in its reading and analysis, given the subjects' daily reality and the socio-cultural scope that the theme enables the strategies of problematization and criticism. Such discursive triggers provided understandings about the specificity of this type of language, differentiation relations with other languages and uses, which demands strategies, rules, procedures, games of possible relations of subject positions and articulation with a series of knowledge domains such as Linguistics, Semiotics, Psychoanalysis, History, Anthropology, Pedagogy. In view of this derivative tree, the present research found the thesis that humor design is a type of language existing in the field of popular education, which corroborates to facilitate the nexus between education, culture and politics in the process of formation and awareness of educated subjects in a synthetic and critical way; and its pedagogical use encompasses procedures such as cultural synthesis, world reading, critical reflection, problematization and dialogue.